2018
DOI: 10.14336/ad.2017.0328
|View full text |Cite
|
Sign up to set email alerts
|

TOPK Promotes Microglia/Macrophage Polarization towards M2 Phenotype via Inhibition of HDAC1 and HDAC2 Activity after Transient Cerebral Ischemia

Abstract: T-LAK-cell-originated protein kinase (TOPK) is a newly identified member of the mitogen-activated protein kinase family. Our previous study has showed that TOPK has neuroprotective effects against cerebral ischemia-reperfusion injury. Here, we investigated the involvement of TOPK in microglia/ macrophage M1/M2 polarization and the underlying epigenetic mechanism. The expression profiles, co-localization and in vivo interaction of TOPK, M1/M2 surface markers, and HDAC1/HDAC2 were detected after middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Additional studies with a larger sample size are needed to validate our findings. Moreover, we identified M1‐ and M2‐like M/MΦ only by using surface markers, such as CD45, CD11b, CD86, and CD206, as indicated in animals . Monocytes, macrophages, and microglia have large overlap in surface markers including CD11b, CD86, and CD206.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies with a larger sample size are needed to validate our findings. Moreover, we identified M1‐ and M2‐like M/MΦ only by using surface markers, such as CD45, CD11b, CD86, and CD206, as indicated in animals . Monocytes, macrophages, and microglia have large overlap in surface markers including CD11b, CD86, and CD206.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified M1-and M2like M/MΦ only by using surface markers, such as CD45, CD11b, CD86, and CD206, as indicated in animals. 52,75,88 Monocytes, macrophages, and microglia have large overlap in surface markers including CD11b, CD86, and CD206. There is currently no consensus on how to identify resident microglia and infiltrating myeloid cells using specific surface markers under inflammatory conditions.…”
Section: F I G U R E 4 Influence Of Time From Symptom Onset To Mis Lmentioning
confidence: 99%
“…CIP promotes TOPK phosphorylation, significantly enhances TOPK activity, and reduces reperfusion injury (Zhao et al, 2014a). Further findings suggest that TOPK positively regulates microglia/macrophage M2 polarization by inhibiting histone deacetylase (HDAC) 1/HDAC2 activity, which regulated inflammatory responses by participating in the microglia/macrophages M1/M2 polarization (Wang et al, 2015;Zhao et al, 2016;Han et al, 2018), and may contribute to its neuroprotective effects against CIRI (Han et al, 2018). Previous mechanism studies have shown that ERK is the downstream signal of TOPK, and that the PI3K/PTEN/Akt and PBK signaling pathways are also involved in the TOPK regulation process (Gao et al, 2016;Sun et al, 2016).…”
Section: Sirt/foxo Signaling Pathwaymentioning
confidence: 97%
“…HDAC2 belongs to the class I HDACs and is known to act as epigenetic and transcriptional regulators. It was already known that HDAC2 could regulate the phenotype shift of T helper cells, microglia, and macrophages 13‐15 . However, whether miR‐494 and its target HDAC2 are implicated in brain infiltration of neutrophil or phenotypic transformation following ischemic stroke is not clear.…”
Section: Introductionmentioning
confidence: 99%